Discordance between physical symptoms versus perception of severity by women with nausea and vomiting in pregnancy (NVP) - Koren Gideon; Magee Laura; Chandra Kiran (BMC, 2002)
Abstract Background Nausea and vomiting in pregnancy (NVP) is a multifaceted condition that affects more than half of pregnant women and can range in severity from mild nausea to severe dehydration. Presently physicians evaluate mostly physical symptoms of NVP in trying to assess the severity of the condition. The objective of this study was to investigate how factors, other than the physical morbidity of nausea and vomiting, influence self-perception of NVP by affected women. Methods Five hundred women with NVP calling a 1-800 NVP Healthline were asked to rate their NVP severity and report their nausea duration and number of vomiting/retching episodes. Results Nausea and vomiting/retching correlated significantly but very poorly with self-assessment of NVP severity. There was also a correlation between nausea duration and vomiting/retching frequency however the correlations were weak and overall physical symptoms could only explain 14% of the variability of women's feelings and perceptions through multivariate analysis. Conclusions Physical symptoms weakly correlate with self-assessment of NVP severity. Other aspects of this condition, most probably psychosocial, influence women's perception of NVP severity.